Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.abb.2007.08.033
|View full text |Cite
|
Sign up to set email alerts
|

A polymer physics perspective on driving forces and mechanisms for protein aggregation

Abstract: Protein aggregation is a commonly occurring problem in biology. Cells have evolved stress-response mechanisms to cope with problems posed by protein aggregation. Yet, these quality control mechanisms are overwhelmed by chronic aggregation-related stress and the resultant consequences of aggregation become toxic to cells. As a result, a variety of systemic and neurodegenerative diseases are associated with various aspects of protein aggregation and rational approaches to either inhibit aggregation or manipulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
172
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 156 publications
(185 citation statements)
references
References 103 publications
(122 reference statements)
9
172
0
2
Order By: Relevance
“…Here, T denotes temperature, and k is Boltzmann's constant. The radius of gyration of a g residue blob scales as g 1/2 , and for sequences lacking in proline residues, g ∼ 5 (20). The overall charge asymmetry is defined as , such that 0 ≤ κ ≤ 1.…”
Section: Resultsmentioning
confidence: 99%
“…Here, T denotes temperature, and k is Boltzmann's constant. The radius of gyration of a g residue blob scales as g 1/2 , and for sequences lacking in proline residues, g ∼ 5 (20). The overall charge asymmetry is defined as , such that 0 ≤ κ ≤ 1.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the concepts underlying protein aggregation might be similar to those describing the organization of synthetic polymers, which may explain some features of the growth-kinetic processes [2]. A recent study has put forward a general unifying mechanism based on the formulation of master equations that describe the kinetics of fibrillar self-assembling as resulting from three basic processes: i) a nucleationdependent polymerization reaction (lag-phase), usually slower than the ii) elongation of preexisting nuclei, and finally iii) a secondary nucleation event deriving from the fragmentation of fibrils [3].…”
Section: Introductionmentioning
confidence: 99%
“…The aggregation process is often characterized by the presence of one or more threshold concentrations at which a sharp, discontinuous change to some aspect of the assembly state (e.g., size, conformational characteristics, material properties) occurs (3)(4)(5)(6). Such a change can be described using the concepts of phase transitions.…”
mentioning
confidence: 99%
“…Phase separation, a subcategory of phase transitions, has recently received considerable attention due to increasing recognition of its importance in cell biology (7)(8)(9)(10)(11)(12)(13). Phase separation refers to aggregation-related changes in molecular density that give rise to the coexistence of dilute macromolecule-deficient phases and dense macromolecule-rich phases (3,14,15). Examples of multiple coexisting phases have been observed in biological contexts (15)(16)(17)(18), and these phases can be liquid, solid, or semisolid (e.g., a gel) (10,(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%